Joining in public discussion : a study of effective speechmaking for members of labor unions, conferences, forums and other discussion groups - Sheffield, Alfred Dwight (New York: George H. Doran Company, 1922)
"by Alfred Dwight Sheffield Bibliotheek Camille Huysmans"